ESTABLISHING REFERENCE INTERVALS FOR SELECTED HEMATOLOGICAL PARAMETERS IN PREGNANT WOMEN AT HUNG YEN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To establish reference intervals for selected peripheral blood cell parameters among pregnant women by gestational stage at Hung Yen Obstetrics and Pediatrics Hospital. Subjects and methods: A cross-sectional descriptive study was conducted using retrospective complete blood count data from 1376 pregnant women attending the hospital, including 260 women in the first trimester, 260 in the second trimester, and 856 in the third trimester. Reference intervals were determined for each parameter and gestational stage using a non-parametric method based on the 2,5th and 97,5th percentiles. Results: The reference intervals for HGB were 86,0–142,6, 88,4–142,0, and 90,0–139,0 g/L in the first, second, and third trimesters, respectively. WBC showed the highest upper reference limit in the third trimester, reaching 20,45 G/L. PLT had the lowest lower reference limit in the third trimester, at 134,0 G/L. Neutrophil-related parameters and several red blood cell indices also varied across gestational stages. Conclusion: This study provides preliminary reference data to support hematological interpretation in pregnant women at the study site and contributes to the stepwise development of gestational stage-specific reference intervals for routine laboratory practice.
Keywords: Reference interval; peripheral blood cells; pregnancy; Celltac F.